The Effects of Fluency Enhancing Conditions on Sensorimotor Control of Speech in Typically Fluent Speakers: An EEG Mu Rhythm Study - Kittilstved, Tiffani; Reilly, Kevin J.; Harkrider, Ashley W.; Casenhiser, Devin; Thornton, David; Jenson, David E.; Hedinger, Tricia; Bowers, Andrew L.; Saltuklaroglu, Tim (Frontiers in Human Neuroscience, 2018)
Objective: To determine whether changes in sensorimotor control resulting from speaking conditions that induce fluency in people who stutter (PWS) can be measured using EEG mu rhythms in neurotypical speakers. Methods: Non-stuttering adults spoke in one control condition (solo speaking) and four experimental conditions (choral speech, delayed auditory feedback (DAF), prolonged speech, and pseudostuttering). Independent component analysis (ICA) was used to identify sensorimotor µ components from EEG recordings. Time-frequency analyses measured µ-alpha (8-13 Hz) and µ-beta (15-25 Hz) event-related synchronization (ERS) and desynchronization (ERD) during each speech condition. Results: 19/24 participants contributed µ components. Relative to the control condition, the choral and DAF conditions elicited increases in µ-alpha ERD in the right hemisphere. In the pseudostuttering condition, increases in µ- beta ERD were observed in the left hemisphere. No differences were present between the prolonged speech and control conditions. Conclusions: Differences observed in the experimental conditions are thought to reflect sensorimotor control changes. Increases in right hemisphere µ-alpha ERD likely reflect increased reliance on auditory information, including auditory feedback, during the choral and DAF conditions. In the left hemisphere, increases in µ-beta ERD during pseudostuttering may have resulted from the different movement characteristics of this task compared with the solo speaking task. Relationships to findings in stuttering are discussed. Significance:  Changes in sensorimotor control related feedforward and feedback control in fluency-enhancing speech manipulations can be measured using time-frequency decompositions of EEG µ rhythms in neurotypical speakers.  This quiet, non-invasive and temporally sensitive technique may be applied to learn more about normal sensorimotor control and fluency enhancement in PWS.